Hemolymph iron in Crustacea decapoda during the intermolt cycle (Revista Española de Fisiología, 1976)
A study on the iron content in the hemolymph of Austropotamobius pallipes and Carcinus maenas has been made. The hemolymph iron content and the total iron binding capacity were investigated in males and females of both species. The values obtained for hemolymph iron content in the males were between 154 and 430 mug/100/ml and in the females between 134 and 431 mug/100/ml. The total iron binding capacity for the males was between 472 and 762 mug/100/ml and for the females between 390 and 698 mug/100/ml. The variations occurring in both parameters during different stages of the intermolt were also studied. The first increase in hemolymph iron coincides with the postmolt stage. During the intermolt, the need for iron decreases as the rate of tissue synthesis becomes lower. Finally an enormous increase in the hemolymph iron content was observed during the molt.